Factor influencing Gen Z preferred working environment in Malaysia - Aziz, Faiq; Abdul Rashid, Mas Anom; Azman Othman, Mohd Noor; Ismail, Ida Rosnita (Ninety Nine Publication, 2021)
Managing the working environment expected by Generation Z is an important element which needs to be addressed by an organization because they are able to project positive impact to the organizational objective and image. Organizations worldwide are now demanding for potential workforce that has extraordinary qualities to manage and lead them towards exceptional success. Workers with good characteristic, measurable expectation, positive leadership attributes and sound communication skills are seen to be the preferred workforce to spearhead the new challenges in achieving the organization’s objectives. This research employs an exploratory research methodology to explore the factors influencing the relationship between Generation Z characteristic, expectation, preferred communication and preferred leadership towards preferred work environment from the students’ perspective at a private college in Malaysia. Data were collected from 327 students studying at a private college to gauge their preferences related to the working environment they hope to be part of in the future. The results show that the relationships between the variables are strong and positively related to each other. For further understanding, future studies are recommended to explore the findings of this study by doing a comparative analysis across institutions and sectors.